EFFECT OF INTERPERSONAL COMMUNICATION TRAINING PROGRAM ON CHILD’S IMMUNIZATION AMONG MOTHERS LIVING IN KEBBI STATE OF NIGERIA - Basheer, Saudat Abdullahi; Kumar, Ramesh; Viwattanakulvanid, Pramon; Muhammad Basheer Yaha; Somrongthong, Ratana (Journal of Ayub Medical College Abbottabad, 2021)
Background: Sharing of information through health education training of mothers on child vaccination has proved an effective intervention for better outcome and increased immunization coverage. This study aimed to examine the effect of interpersonal communication (IPC) training program on mothers’ knowledge of child’s vaccination and routine childhood immunization uptake in local government areas (LGAs) of Kebbi State, Nigeria. Methods: A quasi-experimental study was conducted in two local government areas in Kebbi State, from October 2016 to March 2017. Four hundred twenty mothers participated in the study and were allocated equally (210) in both intervention and control group (n=210) and data were collected on vaccination status of the children after intervention from children’s vaccination cards and mother’s verbal reports. Independent t test and Chi-square were used to test the effect of intervention on mother’s knowledge of child’s vaccination and routine childhood immunization uptake between intervention and control group. Study was ethically approved from the review board of Ministry of Health, Nigeria. Results: Mean knowledge scores has improved in the intervention group (M = 5.42, SD = 3.35) and control group (M=1.96, SD=2.37) after intervention with p<0.001. Routine childhood immunization uptake fully immunized (53.8% vs. 9.5%), partially immunized (16.6% vs. 32.8%) and un-immunized (29.5% vs. 57.6%) in both group after intervention with p<0.001. Approximately fifty-four percentages of children in the intervention group were fully immunized after intervention. However, there was minimal change of 2% has been observed in control group. Percentage of unimmunized children was high in both groups at pre-intervention (66%) but this decreased to 29.5% in the intervention group and 57.6% in the control group. Conclusion: This study concludes that, IPC skill is an effective intervention and a sustainable service for improving the knowledge and uptake of mother’s face-to-face education, social mobilization and reminder services about routine childhood immunization within entire population. Keywords: Immunization; Effectiveness; Knowledge; interpersonal communication skills and training